Continuous microfluidic encapsulation of single mesenchymal stem cells using alginate microgels as injectable fillers for bone regeneration. (15th July 2020) - An, Chuanfeng; Liu, Weijian; Zhang, Yang; Pang, Bo; Liu, Hui; Zhang, Yujie; Zhang, Haoyue; Zhang, Liyuan; Liao, Hongbing; Ren, Changle; Wang, Huanan
Abstract: The encapsulation of cells in microscale hydrogels can provide a mimic of a three-dimensional (3D) microenvironment to support cell viability and functions and to protect cells from the environmental stress, which have been widely used in tissue regeneration and cell therapies. Here, a microfluidics-based approach is developed for continuous encapsulation of mesenchymal stem cells (MSCs) at the single-cell level using alginate microgels. This microfluidic technique integrated on-chip encapsulation, gelation, and de-emulsification into a one-step fabrication process, which enables scalable cell encapsulation while retaining the viability and functionality of loaded cells. Remarkably, we observed MSCs encapsulated in Ca-alginate microgels at the single-cell level showed significantly enhanced osteogenesis and accelerated mineralization of the microgels which occurred only after 7 days of induction. Furthermore, MSCs laden in alginate microgels displayed significantly enhanced bone formation compared to MSCs mixed with microgels and acellular microgels in a rat tibial ablation model. To conclude, the current microfluidic technique represents a significant step toward continuous single cell encapsulation, fabrication, and purification. These microgels can boost bone regeneration by providing a controlled osteogenic microenvironment for encapsulated MSCs and facilitate stem cell therapy in the treatment of bone defects in a minimally invasive delivery way. Statement of Significance: The biological functions and therapeutic activities of single cells laden in microgels for tissue engineering remains less investigated. Here, we reported a microfluidic-based method for continuous encapsulation of single MSCs with high viability and functionality by integrating on-chip encapsulation, gelation, and de-emulsification into a one-step fabrication process. More importantly, MSCs encapsulated in alginate microgels at the single-cell level showed significantly enhanced osteogenesis, remarkably accelerated mineralization in vitro and bone formation capacity in vivo . Therefore, this single-cell encapsulation technique can facilitate stem cell therapy for bone regeneration and be potentially used in a variety of tissue engineering applications. Graphical Abstract: Image, graphical abstract